An assessment of the potential risks of Transfusion Transmitted Infections in patients transfused in Zimbabwean Hospitals - Rutsate, Ruvimbo; Mandisodza, Arthur; Chikwash, Vasco; Emmanuel, Jean; Mavunganidze, George; Nkomo, Sisodwa (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2017)
Blood safety remains the main objective for pretransfusion testing procedures. For the safety of patients, blood is routinely tested for infectious agents in donated blood such as HIV, HBV, HCV and Syphilis. A retrospective study to determine the seroprevalence and trends of HIV, HBV, HCV and Syphilis in donated blood was carried out by reviewing records of the Zimbabwean donors from January 2013 to December 2016. The prevalence of TTIs declined during this study period. HIV and HBV showed a significant decrease due to improved donor selection criteria. There was no HCV detection from 2013. Other studies also showed declining HCV concentrations. Syphilis increased during the same period. Despite the noted decline, the risk of TTIs remains high. There is need to reduce this risk in transfused patients by the introduction of the highly sensitive nucleic acid testing (NAT) test in Zimbabwe to improve on the detection TTIs in donated blood.